Kegiatan Penyuluhan 4 Sehat 5 Sempurna SD MI Amiroh Jakarta - Salman naning; Mira Ziveria (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2022)
Food for 4 healthy 5 perfect is a lifestyle that has been done by some people. The habit of eating healthy food in the future will help the community, especially children, to grow up happy and healthy and be a form of contribution to preventing health problems in the future. This 4 healthy 5 perfect food campaign then became the basis of the implementation of the PKM program with the title "4 Healthy 5 Perfect Counseling Activities at Mi Amiroh Elementary School Jakarta". This activity involved 70 Mi Amiroh Elementary School students, including grades 2 and 5 of elementary school. This PKM activity uses a qualitative approach and the theory used in the implementation of this activity is the theory of innovation diffusion using descriptive analysis. The results obtained are that there is enthusiasm from the students and has fulfilled the aspects of planning a good program evaluation.